Positive conductive paste, preparation method thereof and positive plate

By adding single-wall carbon nanotubes, carbon black conductive agents, softener and dispersed cracking-proof additives to the positive electrode conductive paste, a three-dimensional conductive network is built and the rheological characteristics are improved, and the problems of high compaction density of lithium iron phosphate and thick coated electrode sheets are solved, which is easy to crack and poor brittleness in the direction of the electrode sheets, which significantly improves the performance of the electrode sheets and battery cells.

CN119650702APending Publication Date: 2025-03-18SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411974364.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the development of the existing high compaction density of lithium iron phosphate and thick coated electrode sheets, there are problems such as easy cracking of the electrode sheet, poor brittleness of the roller pressure electrode sheet, easy breaking of the roller pressure belt, cracking of the inner folding R angle of the heat-piezoelectric core, and difficulty in infiltration of the battery cell, as well as poor fast charging performance.

Method used

A positive electrode conductive paste is used, which includes 0.02% to 0.05% single-wall carbon nanotubes, 0.3% to 0.7% carbon black conductive agent, 0.1% to 0.5% softener, 0.1% to 0.5% dispersed crack-proof integrated additive, 96% to 98% positive electrode active material, and 1% to 2.25% binder. The slurry improves the conductivity and flexibility of the pole sheet by building a three-dimensional conductive network and improving rheological characteristics.

Benefits of technology

It significantly improves the production efficiency and performance of the electrode sheet, avoids brittle fracture, optimizes the conductivity and charge and discharge performance of the battery cell, solves problems such as easy cracking, poor brittleness, and light transmission in hot pressing, and improves fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650702A_ABST
    Figure CN119650702A_ABST
Patent Text Reader

Abstract

The invention provides positive conductive paste, a positive plate and a lithium ion battery. The positive electrode conductive paste comprises a solid and a solvent, and the positive electrode conductive paste comprises the following components in percentage by mass of the solid: 0.02%-0.05% of a single-walled carbon nanotube, 0.3%-0.7% of a carbon black conductive agent, 0.1%-0.5% of a softening agent, 0.1%-0.5% of a dispersing and anti-cracking integrated auxiliary agent, 96%-98% of a positive electrode active material and 1%-2.25% of a binder. By adding the single-walled carbon nanotubes, the conductivity and mechanical properties of the positive electrode conductive paste are improved. And the softening agent improves the rheological property of the positive electrode conductive paste and enhances the flexibility of the pole piece at the same time. And the dispersing and anti-cracking integrated auxiliary agent effectively disperses positive electrode active material particles and prevents coating and baking cracking. The high solid content achieved under the cooperative work of the three is beneficial to solving the problems of brittle failure, low coating rate, easy cracking of the pole piece and the like of the thick pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive pastes, and in particular to a positive electrode conductive paste, a positive electrode sheet and a lithium ion battery. Background Art

[0002] In recent years, lithium-ion batteries (LIBs) have become the mainstream choice in the fields of consumption, power and new energy storage. Their application has promoted the grid connection and utilization of renewable energy, and has made outstanding contributions to the realization of the "dual carbon" goal and the development of a sustainable society. With the growing demand for high energy density, the development of high-energy-density lithium-ion batteries has become a major direction for battery suppliers. Among them, the development of high-energy-density lithium iron phosphate batteries is mainly divided into three major directions. The first is high-working voltage platform lithium iron phosphate derivative materials, such as lithium iron manganese phosphate. The second is to increase the mass proportion of active materials in the lithium iron phosphate electrode formula, such as introducing conductive adhesives to reduce the content of adhesives or conductive agents. The third is to increase the thickness of the pole piece and reduce the volume proportion of auxiliary materials such as current collectors and diaphragms. People have been conducting in-depth research and development in various directions to discover the most suitable new materials or technologies.

[0003] At present, except for lithium iron manganese phosphate, which is relatively stable among lithium iron phosphate derivative materials, the performance maturity of other materials is not enough. The increase in the proportion of main materials has almost reached a bottleneck. At present, people's development of high compaction density of lithium iron phosphate with thick coating pole pieces is relatively mature, and it is also the easiest direction to achieve mass production in terms of high energy density batteries. Development direction for the high compaction density of existing lithium iron phosphate and its derivative materials with thick coating pole pieces. The main problems are concentrated in the low pole piece coating speed in the front section, easy cracking of the pole piece, poor brittleness of the rolled pole piece, easy breaking of the rolling belt, cracking and light transmission of the hot pressing inner folded R angle of the wound battery cell in the back section, difficulty in cell infiltration and other manufacturing process window problems, as well as electrical properties such as poor fast charging performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a positive electrode conductive slurry, a preparation method thereof, and a positive electrode sheet, so as to solve the problems in the prior art such as easy cracking of the electrode sheet, poor brittleness of the rolled electrode sheet, easy breakage of the electrode sheet during rolling, cracking and light transmission due to the folded R angle inside the hot-pressed battery cell, difficulty in wetting the battery cell, and poor manufacturing process window and fast charging performance.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a positive electrode conductive slurry is provided, which comprises, by solid mass percentage, 0.02% to 0.05% of single-walled carbon nanotubes, 0.3% to 0.7% of carbon black conductive agent, 0.1% to 0.5% of softener, 0.1% to 0.5% of dispersion and anti-cracking integrated auxiliary agent, 96% to 98% of positive electrode active material and 1% to 2.25% of binder.

[0006] Furthermore, the solid content of the above-mentioned positive electrode conductive slurry is 60% to 70%, and / or the viscosity of the positive electrode conductive slurry is 4000 to 30000 mPa.s, and the fineness of the positive electrode conductive slurry is less than 30 μm; and / or the solvent is N-methylpyrrolidone; and / or during the coating process of the positive electrode conductive slurry, when the positive electrode conductive slurry is coated at a coating rate of 20 m / min to 100 m / min, the obtained positive electrode sheet maintains an appearance without cracks.

[0007] Furthermore, the structural formula of the above-mentioned softener is:

[0008]

[0009] Wherein, the main chain is selected from any one of the polyether linear segments of ethylene oxide, propylene oxide, and butylene oxide homopolymer or copolymer; R 1 Selected from carboxyl, hydroxyl and NH 4+ Any easily ionizable small molecule polar group; R 2 C 1 ~C 100 Linear polyester segments or C 1 ~C 100 linear polyether segment; preferably the molecular weight of the softener is 10,000 to 500,000.

[0010] Furthermore, the above-mentioned dispersing and crack-preventing integrated auxiliary agent is a polyphosphate dispersant and / or a polysulfonate dispersant, and the structural formula of the polymerized monomer of the polyphosphate dispersant is:

[0011]

[0012] Among them, R 1 Any one selected from carboxyl, hydroxyl and hydrogen; R 2 C 1 ~C 50 Linear polyolefin segments; R 3 Part of the benzene ring is irregularly substituted with C 1 ~C 50 linear polyether segment; preferably the molecular weight of the polyphosphate dispersant is 10,000 to 500,000.

[0013] Furthermore, the positive electrode active material is a lithium iron phosphate material containing a carbon coating layer.

[0014] Furthermore, the carbon black conductive agent is conductive carbon black and / or superconducting carbon black.

[0015] Furthermore, the above-mentioned adhesive is an adhesive obtained by copolymerization of polytetrafluoroethylene and hexafluoropropylene or a PVDF adhesive.

[0016] According to another aspect of the present invention, a positive electrode sheet is provided, comprising a positive electrode current collector and a positive electrode active material coating, wherein the positive electrode active material coating is obtained by coating a conductive slurry on the positive electrode current collector and then drying the conductive slurry, and the conductive slurry is the positive electrode conductive slurry mentioned above.

[0017] Furthermore, the coating double-sided density of the positive electrode sheet is greater than 500g / m 2 , compaction density> 2.5g / cc, the positive electrode sheet after rolling, the peeling force after rolling is greater than 5N / m, the film resistance after rolling is less than 1mΩ, and the surface density is extended to 4-10g / m 2 ; and / or the positive electrode sheet is manually folded and rolled at least 4 times without cracking and light transmission; and / or the length extension rate of the positive electrode sheet in the tape running direction is 0.5% to 1.5%, and the width extension rate of the positive electrode sheet is 0.4 to 1.5 mm.

[0018] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0019] By applying the technical solution of the present invention, the addition of single-walled carbon nanotubes in the positive electrode conductive paste of the present application utilizes its high aspect ratio and flexibility to construct a three-dimensional conductive network, thereby improving the conductivity and mechanical properties of the positive electrode conductive paste. The role of the softener is to improve the rheological properties of the positive electrode conductive paste, so that the positive electrode conductive paste still maintains good coating performance at a high solid content, while enhancing the flexibility of the pole piece. The dispersed anti-cracking integrated auxiliary agent effectively disperses the positive electrode active material particles and prevents cracking through the action of its polar groups on the surface of the positive electrode active material, while maintaining the viscosity and solid content of the positive electrode conductive paste. The high solid content achieved by the synergistic work of the above three is conducive to significantly improving the process efficiency, the flexibility of the pole piece avoids the brittle fracture of the pole piece under high compaction density, and the optimization of the pole piece conductive network improves the conductivity and charge and discharge performance of the battery cell. The synergistic effect of all the above components improves the dispersion stability of the positive electrode conductive slurry, and solves the problems of easy cracking of the pole piece, poor brittleness of the rolled pole piece, easy breakage of the belt during rolling, cracking and light transmission of the R angle inside the hot-pressed battery cell, difficulty in cell wetting, and other manufacturing process windows and poor fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0021] Figure 1 The surface density extension of the positive electrode sheet in Example 1 and Comparative Example 1 of the present application is shown;

[0022] Figure 2The width extension of the positive electrode sheet in Example 1 and Comparative Example 1 of the present application is shown;

[0023] Figure 3 The figure shows the number of times the positive electrode sheet is folded and transmits light in Example 1 and Comparative Example 1 of the present application;

[0024] Figure 4 The voltage platform of the battery cells in Example 1 and Comparative Example 1 of the present application is shown;

[0025] Figure 5 The first effect of the battery cells in Example 1 and Comparative Example 1 of the present application is shown;

[0026] Figure 6 The divided capacity discharge capacity of the battery cells in Example 1 and Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0028] As analyzed in the background technology of this application, the pole pieces in the prior art have problems such as easy cracking, poor brittleness of rolled pole pieces, easy breakage of belts during rolling, cracking and light transmission at the R-angle inside the hot-pressed battery cell, difficulty in cell wetting, and poor manufacturing process windows and fast charging performance. In order to solve such problems, the present application provides a positive electrode conductive slurry, a preparation method thereof, and a positive electrode sheet.

[0029] In a typical embodiment of the present application, a positive electrode conductive slurry is provided, which includes, by solid ratio by mass percentage, 0.02% to 0.05% of single-walled carbon nanotubes, 0.3% to 0.7% of carbon black conductive agent, 0.1% to 0.5% of softener, 0.1% to 0.5% of dispersion and anti-cracking integrated auxiliary agent, 96% to 98% of positive electrode active material and 1% to 2.25% of binder.

[0030] The addition of single-walled carbon nanotubes in the positive electrode conductive paste of the present application utilizes its high aspect ratio and flexibility to construct a three-dimensional conductive network, thereby improving the conductivity and mechanical properties of the positive electrode conductive paste. The role of the softener is to improve the rheological properties of the positive electrode conductive paste, so that the positive electrode conductive paste still maintains good coating performance at a high solid content, while enhancing the flexibility of the pole piece. The dispersed anti-cracking integrated auxiliary agent effectively disperses the positive electrode active material particles and prevents cracking through the action of its polar groups on the surface of the positive electrode active material, while maintaining the viscosity and solid content of the positive electrode conductive paste. The high solid content achieved by the synergistic work of the above three is conducive to significantly improving the process efficiency. The flexibility of the pole piece avoids the brittle fracture of the pole piece under high compaction density, and the optimization of the pole piece conductive network improves the conductivity and charge and discharge performance of the battery cell. The synergistic effect of all the above components improves the dispersion stability of the positive electrode conductive slurry, and solves the problems of easy cracking of the pole piece, poor brittleness of the rolled pole piece, easy breakage of the belt during rolling, cracking and light transmission of the R angle inside the hot-pressed battery cell, difficulty in cell wetting, and other manufacturing process windows and poor fast charging performance.

[0031] In addition, the mass percentage of single-walled carbon nanotubes can be 0.02%, 0.021%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%. Of course, the mass percentage of single-walled carbon nanotubes can be any point value within the range of 0.02% to 0.05%. Preferably, the mass percentage of single-walled carbon nanotubes can be any point value within the range of 0.02% to 0.03%, which will not be repeated here.

[0032] The mass percentage of the carbon black conductive agent can be 0.3%, 0.31%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65% or 0.7%. Of course, the mass percentage of the carbon black conductive agent can be any point value within the range of 0.3% to 0.7%. Preferably, the mass percentage of the carbon black conductive agent can be any point value within the range of 0.5% to 0.7%, which will not be repeated here.

[0033] The mass percentage of the softener can be 0.1%, 0.11%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%. Of course, the mass percentage of the softener can be any point value within the range of 0.1% to 0.5%. Preferably, the mass percentage of the softener can be any point value within the range of 0.15% to 0.2%, which will not be repeated here.

[0034] The mass percentage of the dispersed anti-cracking integrated auxiliary agent can be 0.1%, 0.11%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%. Of course, the mass percentage of the dispersed anti-cracking integrated auxiliary agent can be any point value within the range of 0.1% to 0.5%. Preferably, the mass percentage of the dispersed anti-cracking integrated auxiliary agent can be any point value within the range of 0.15% to 0.2%, which will not be repeated here.

[0035] The mass percentage of the positive electrode active material can be 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 97%, 97.5% or 98%. Of course, the mass percentage of the positive electrode active material can be any point value within the range of 96% to 98%. Preferably, the mass percentage of the positive electrode active material can be any point value within the range of 97% to 98%, which will not be repeated here.

[0036] The mass percentage of the binder can be 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or 2.25%. Of course, the mass percentage of the binder can be any point value within the range of 1% to 2.25%. Preferably, the mass percentage of the binder can be any point value within the range of 1.5% to 2%, which will not be repeated here.

[0037] In one embodiment of the present application, the solid content of the above-mentioned positive electrode conductive slurry is 60% to 70%, and / or the viscosity of the positive electrode conductive slurry is 4000 to 30000 mPa.s, and the fineness of the positive electrode conductive slurry is less than 30 μm; and / or the solvent is N-methylpyrrolidone; and / or during the coating process of the positive electrode conductive slurry, when the positive electrode conductive slurry is coated at a coating rate of 20 m / min to 100 m / min, the obtained positive electrode sheet maintains an appearance without cracks.

[0038] The viscosity, fineness and solid content of the positive electrode conductive slurry are preferably controlled within the above ranges, which greatly improves the efficiency of the slurry mixing and coating process, and takes into account the high energy density of the pole piece and the coatability of the positive electrode conductive slurry. The stability and mechanical properties of the positive electrode conductive slurry help the pole piece to improve stability during the coating process.

[0039] In addition, the solid content of the positive electrode conductive paste can be 60%, 60.5%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 67.9%, 68%, 68.1%, 68.2%, 68.3%, 69% or 70%. Of course, the solid content of the positive electrode conductive paste can be any point value within the range of 60% to 70%. Preferably, the solid content of the positive electrode conductive paste can be any point value within the range of 67% to 69%, which will not be repeated here.

[0040] The viscosity of the positive electrode conductive paste can be 4000mPa.s, 4900mPa.s, 5000mPa.s, 5400mPa.s, 5600mPa.s, 5700mPa.s, 6000mPa.s, 7000mPa.s, 8000mPa.s, 9000mPa.s, 10000mPa.s, 20000mPa.s or 30000mPa.s. Of course, the viscosity of the positive electrode conductive paste can be any point value within the range of 4000 to 30000mPa.s. Preferably, the viscosity of the positive electrode conductive paste can be any point value within the range of 4000 to 6000mPa.s. Further preferably, the viscosity of the positive electrode conductive paste can be any point value within the range of 4900 to 5600mPa.s, which will not be repeated here.

[0041] The coating rate can be 20m / min, 25m / min, 30m / min, 40m / min, 50m / min, 60m / min, 70m / min, 80m / min, 90m / min or 100m / min. Of course, the coating rate can be any point value within the range of 20m / min to 100m / min. Preferably, the coating rate can be any point value within the range of 20m / min to 50m / min, which will not be repeated here.

[0042] In one embodiment of the present application, the structural formula of the above-mentioned softener is:

[0043]

[0044] Wherein, the main chain is selected from any one of the polyether linear segments of ethylene oxide (EO), propylene oxide (PO), and butylene oxide (BO) homopolymer or copolymer; R 1 Selected from carboxyl, hydroxyl and NH 4+ Any easily ionizable small molecule polar group; R 2 C 1 ~C 100 Linear polyester segments or C 1 ~C 100 linear polyether segment; preferably the molecular weight of the softener is 10,000 to 500,000.

[0045] R 1 It helps to improve the dispersion and bonding properties of the material by interacting with the polar groups on the surface of the positive electrode active material. 2The introduction of non-polar flexible segments increases the slippage between molecules, thereby improving the rheological properties of the positive electrode conductive slurry and the flexibility of the pole piece. The preferred range of molecular weight ensures that the softener is evenly dispersed in the slurry and effectively exerts its softening effect without affecting other properties of the slurry. Through the structural optimization of the softener, the flexibility of the pole piece is significantly improved, and its stability in the manufacturing process is improved. Furthermore, the preferred model of the softener in this application is YTF2159, the manufacturer is Shenzhen Yite Technology Co., Ltd., and the solid content is 50%.

[0046] In addition, the molecular weight of the softener can be 10000, 20000, 50000, 100000, 150000, 200000, 300000, 400000 or 500000. Of course, the molecular weight of the softener can be any point value within the range of 10000 to 500000, which will not be repeated here.

[0047] In one embodiment of the present application, the above-mentioned dispersing and crack-preventing integrated auxiliary agent is a polyphosphate dispersant and / or a polysulfonate dispersant, and the structural formula of the polymerized monomer of the polyphosphate dispersant is:

[0048]

[0049] Among them, R 1 Any one selected from carboxyl, hydroxyl and hydrogen; R 2 C 1 ~C 50 Linear polyolefin segments; R 3 Part of the benzene ring is irregularly substituted with C 1 ~C 50 linear polyether segment; preferably the molecular weight of the polyphosphate dispersant is 10,000 to 500,000.

[0050] The use of polyphosphate dispersants promotes affinity with lithium iron phosphate particles, utilizes the interaction between the grafted polar small molecule groups and the surface of the positive active material and the rest of the slurry system, and utilizes the grafted oily linear short chains to provide steric hindrance, which can enhance the dispersibility and stability of each component in the positive conductive slurry as a whole. In addition, the preferred condition of selecting a molecular weight of less than 500,000 improves the dispersibility of the additive in the slurry and reduces the risk of poor dispersion due to excessive molecular weight. Furthermore, the preferred model of the dispersing and cracking-proof integrated additive in this application is YTF3508, the manufacturer is Shenzhen Yite Technology Co., Ltd., and the solid content is 50%.

[0051] In addition, the molecular weight of the polyphosphate dispersant can be 10,000, 20,000, 50,000, 100,000, 150,000, 200,000, 300,000, 400,000 or 500,000. Of course, the molecular weight of the polyphosphate dispersant can be any point value within the range of 10,000 to 500,000, which will not be repeated here.

[0052] In one embodiment of the present application, the positive electrode active material is a lithium iron phosphate material containing a carbon coating layer.

[0053] The use of carbon-coated lithium iron phosphate materials improves the electrochemical performance of the battery cell, especially the charge and discharge efficiency and cycle stability.

[0054] In order to make the battery cell have good conductivity at high energy density, in one embodiment of the present application, it is preferred that the carbon black conductive agent is conductive carbon black and / or superconducting carbon black.

[0055] In one embodiment of the present application, the above-mentioned adhesive is an adhesive obtained by copolymerization of polytetrafluoroethylene and hexafluoropropylene or a PVDF adhesive.

[0056] The adhesive obtained by copolymerization of oily polytetrafluoroethylene and hexafluoropropylene has good bonding performance and softening effect, and is particularly suitable for the preparation of high-density and high-density electrodes. The choice of adhesive has a direct impact on the fluidity, dispersibility and drying performance of the slurry, ensuring uniform coating and efficient drying of the electrode. The reasonable combination of the above types of adhesives and solvents is preferred to improve the stability and coating performance of the slurry during the preparation process, which is conducive to improving production efficiency and product quality.

[0057] In another typical embodiment of the present application, a positive electrode sheet is provided, comprising a positive electrode current collector and a positive electrode active material coating, wherein the positive electrode active material coating is obtained by coating a conductive slurry on the positive electrode current collector and then drying the conductive slurry, and the conductive slurry is the above-mentioned positive electrode conductive slurry.

[0058] The use of the above positive electrode conductive slurry is beneficial to improving the performance of the positive electrode sheet, including high surface density, high compaction density, good peeling force and low resistance, and enhancing the energy density and rate performance of the battery cell.

[0059] In one embodiment of the present application, the coating double-sided density of the above-mentioned positive electrode sheet is greater than 500g / m 2 , compaction density> 2.5g / cc, the positive electrode sheet after rolling, the peeling force after rolling is greater than 5N / m, the film resistance after rolling is less than 1mΩ, and the surface density is extended to 4-10g / m 2 ; and / or the positive electrode sheet is manually folded and rolled at least 4 times without cracking and light transmission; and / or the length extension rate of the positive electrode sheet in the tape running direction is 0.5% to 1.5%, and the width extension rate of the positive electrode sheet is 0.4 to 1.5 mm.

[0060] The optimization of physical performance parameters such as surface density, peel force, and film resistance directly reflects the quality of the positive electrode sheet and the reliability of the battery cell. The elongation and width extension of the positive electrode sheet reflect its good mechanical properties and processing adaptability. The positive electrode sheet maintains integrity after high compaction and multiple folding, which significantly improves the manufacturing window of the battery cell and reduces the risk of common manufacturing defects.

[0061] In addition, the surface density can be extended to 4g / m 2 4.5g / m 2 , 5g / m 2 5.5g / m 2 , 6g / m 2 , 6.5g / m 2 , 7g / m 2 , 7.5g / m 2 , 8g / m 2 , 8.5g / m 2 , 9g / m 2 , 9.5g / m 2 or 10g / m 2 Of course, the surface density can be extended to 4-10g / m 2 Any point value within the range, the preferred surface density extension can be 4 to 6 g / m 2 Any point value within will not be repeated here.

[0062] In addition, the extension rate of the length of the positive electrode sheet in the running direction can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%. Of course, the extension rate of the length of the positive electrode sheet in the running direction can be any point value within the range of 0.5% to 1.5%, which will not be repeated here.

[0063] In addition, the widthwise extension of the positive electrode sheet can be 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1g / mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm or 1.5mm. Of course, the widthwise extension of the positive electrode sheet can be any point value within the range of 0.4 to 1.5mm. Preferably, the widthwise extension of the positive electrode sheet can be any point value within the range of 0.4 to 0.5mm, which will not be repeated here.

[0064] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0065] Lithium-ion batteries have been significantly improved in terms of energy density, charge and discharge efficiency, cycle stability and safety. The optimization of the overall performance of lithium-ion batteries meets the market demand for higher performance, safer and more economical energy storage solutions.

[0066] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0067] Example 1

[0068] The wet process slurry preparation of the double planetary (200L) equipment includes the following steps:

[0069] Add 77.49 kg NMP solvent, add 3.13 kg homopolymer PVDF (HSV900), add 1.23 kg single-walled carbon nanotubes (TUBALL BATT NMP 900, solid content is 4%), add 0.99 kg conductive carbon black (LIX300), rotate at 25 RPM, rotate at 800 RPM, and the time is 10 min;

[0070] Add 0.49 kg of softener (model: YTF2159, manufactured by Shenzhen Yite Technology Co., Ltd., solid content: 50%), rotate at 25 RPM, rotate at 500 RPM, and the time is 5 minutes;

[0071] Add 0.49 kg of dispersible anti-cracking integrated additive (model: YTF3508, manufacturer: Shenzhen Yite Technology Co., Ltd., solid content: 50%), rotate at 25 RPM, rotate at 500 RPM, and the time is 5 minutes;

[0072] While stirring, slowly add 160 kg of LFP (lithium iron phosphate) (model GX100, manufacturer: Guoxuan Lujiang Materials Co., Ltd.), revolution 25 RPM, rotation 500 RPM, time 10 minutes;

[0073] The next step is to conduct high-speed dispersion, with a revolution of 25 RPM and a rotation of 1200 RPM for 220 min to obtain a positive electrode conductive slurry.

[0074] Example 2

[0075] The difference from Example 1 is that the dispersant content is increased by 0.05%, and the amounts of LFP (lithium iron phosphate), NMP solvent, homopolymer PVDF, dispersion anti-cracking integrated additive, softener, single-walled carbon nanotube, and conductive carbon black are 160kg, 77.53kg, 3.13kg, 0.66kg, 0.49, 1.24kg, and 0.99kg, respectively, to finally obtain a positive electrode conductive slurry.

[0076] Example 3

[0077] The difference from Example 1 is that the content of the softener is increased by 0.05%, and the amounts of LFP (lithium iron phosphate), NMP solvent, homopolymer PVDF, dispersed anti-cracking integrated additive, softener, single-walled carbon nanotube, and conductive carbon black are 160kg, 77.53kg, 3.13kg, 0.49kg, 0.66kg, 1.24kg, and 0.99kg, respectively, to finally obtain a positive electrode conductive slurry.

[0078] Example 4

[0079] The difference from Example 1 is that the single-walled carbon nanotubes are reduced by 0.01%, and the amounts of LFP (lithium iron phosphate), NMP solvent, homopolymer PVDF, dispersed anti-cracking integrated additive, softener, single-walled carbon nanotubes, and conductive carbon black are 160kg, 77.52kg, 3.13kg, 0.49kg, 0.49kg, 0.82kg, and 0.99kg, respectively, to finally obtain a positive electrode conductive slurry.

[0080] Comparative Example 1

[0081] The wet process slurry preparation of the double planetary (200L) equipment includes the following steps:

[0082] Add 92.34 kg NMP solvent, add 3.12 kg homopolymer PVDF (HSV900), rotate at 25 RPM, rotate at 1000 RPM, and the time is 60 min;

[0083] Add 1.23 kg of single-walled carbon nanotubes (TUBALL BATT NMP 900 0.4%) and 0.98 kg of conductive carbon black (LIX300), rotate at 25 RPM and 800 RPM for 10 min;

[0084] While stirring, slowly add 160 kg of LFP (lithium iron phosphate) (GX100, Guoxuan Lujiang Materials Co., Ltd.), revolution 25 RPM, rotation 500 RPM, time 10 min;

[0085] The next step is to conduct high-speed dispersion, with a revolution of 25 RPM and a rotation of 1200 RPM for 220 min to obtain a positive electrode conductive slurry.

[0086] Comparative Example 2

[0087] The difference from Example 1 is that no dispersant is added, and the amounts of LFP (lithium iron phosphate), NMP solvent, homopolymer PVDF, softener, single-walled carbon nanotubes, and conductive carbon black are 160 kg, 92.48 kg, 3.12 kg, 0.49 kg, 1.23 kg, and 0.99 kg, respectively, to finally obtain a positive electrode conductive slurry.

[0088] Comparative Example 3

[0089] The difference from Example 1 is that no softener is added, and the amounts of LFP (lithium iron phosphate), NMP solvent, homopolymer PVDF, dispersant, single-walled carbon nanotubes, and conductive carbon black are 160 kg, 77.37 kg, 3.12 kg, 0.49 kg, 1.23 kg, and 0.99 kg, respectively, to finally obtain a positive electrode conductive slurry.

[0090] Comparative Example 4

[0091] The difference from Example 1 is that single-walled carbon nanotubes are not added, and the amounts of LFP (lithium iron phosphate), NMP (GN001) solvent, homopolymer PVDF, LFP, dispersed anti-cracking integrated additive, softener, and conductive carbon black are 160kg, 77.46kg, 3.13kg, 0.49kg, 0.49kg, and 0.99kg, respectively, to finally obtain a positive electrode conductive slurry.

[0092] The solid content, viscosity, fineness and light transmission folding times of the positive electrode conductive pastes obtained in the above examples and comparative examples are listed in Table 1, respectively.

[0093] Table 1

[0094] Implementation / Comparative Example Viscosity (mPa.s) Solid content (%) Fineness(μm) Transparent fold times Example 1 5600 68.30 12 4 Example 2 5400 68.20 12 4 Example 3 5700 67.90 14 5 Example 4 4900 68.10 14 4 Comparative Example 1 5100 64.2 15 2 Comparative Example 2 5600 64.10 12 3 Comparative Example 3 5400 67.90 14 2 Comparative Example 4 5600 68.10 14 2

[0095] The positive electrode conductive pastes obtained in Example 1 and Comparative Example 1 were used to prepare positive electrode sheets respectively:

[0096] The performance of the positive electrode single-layer extrusion coating equipment and the produced electrode sheet includes the following aspects:

[0097] Extrusion coating equipment drying 35m@7 sections;

[0098] The double-sided density of the coated pole piece is 534g / m 2 ;

[0099] Among them, the coating speed of comparative examples 1-2 is 15m / min, and the coating appearance is cracked in large quantities, and the debugging space is limited, the equipment capacity is insufficient, and the pole piece keeps cracking. In the same oven, the coating speed of comparative examples 3-4 and embodiments 1-4 is 20m / min, which can keep the appearance without cracking.

[0100] Among them, the NMP residual content of the coated pole pieces in each comparative example and embodiment is less than 1000ppm, and the weight loss test value is less than 0.5%, which meets the process requirements; the pole piece roller compaction density is 2.55±0.2g / cc, and the peeling force after rolling is greater than 7N / m, which meets the process requirements.

[0101] Among them, in each comparative example and embodiment, the density of the pole piece after rolling is extended to 4-10g / m 2The extension rate of the pole piece length in the walking direction is 0.8-1%, and the extension rate in the width direction is 0.3-0.7 mm, which meets the process requirements.

[0102] Among them, in each comparative example and embodiment, the median resistance of the diaphragm after rolling of the pole piece is 0.66 (<1mΩ), which meets the process requirements. After rolling, Example 1 is folded 4 times to allow light to pass through, and Example 3 is folded 5 times to allow light to pass through (each group in the comparative example is 2 to 3 times to allow light to pass through). The flexibility of each experimental group is improved to a certain extent by changing the formulation system.

[0103] The surface density extension of the positive electrode sheet of Example 1 (the experimental group in the figure, wherein the first group, the second group and the third group represent three parallel implementation tests) and Comparative Example 1 (the control group in the figure, wherein the first group, the second group and the third group represent three parallel comparative tests) is as follows: Figure 1 As shown; Example 1 (the figure is the experimental group, wherein the first group, the second group and the third group represent three parallel implementation tests) and Comparative Example 1 (the figure is the control group, wherein the first group, the second group and the third group represent three parallel comparative tests) The width extension of the positive electrode sheet is as shown Figure 2 As shown; the number of times the positive electrode sheets of Example 1 and Comparative Example 1 are folded and transmitted light is as follows Figure 3 As shown; the voltage platform of the battery cells of Example 1 (the experimental group in the figure) and Comparative Example 1 (the control group in the figure) is as follows Figure 4 As shown; the first effect of the battery cells of Example 1 (the experimental group in the figure) and Comparative Example 1 (the control group in the figure) is as follows Figure 5 As shown; the discharge capacity of the cells of Example 1 (experimental group in the figure) and Comparative Example 1 (control group in the figure) is shown as Figure 6 shown.

[0104] The positive electrode sheets corresponding to Example 1 and Comparative Example 1 were made into 10Ah soft-pack batteries, using the same type of graphite and electrolyte. The electrical properties of the batteries were tested, as shown in Table 2.

[0105] Table 2

[0106]

[0107] Among them, the discharge platforms of comparative example 1 and embodiment 1 are equivalent, and the first efficiency of embodiment 1 is improved by nearly 3% compared with the comparative example (the coating of the comparative example is cracked in large quantities and cannot be debugged), and the capacity is also improved to a certain extent.

[0108] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0109] The addition of single-walled carbon nanotubes in the positive electrode conductive paste of the present application utilizes its high aspect ratio and flexibility to construct a three-dimensional conductive network, thereby improving the conductivity and mechanical properties of the positive electrode conductive paste. The role of the softener is to improve the rheological properties of the positive electrode conductive paste, so that the positive electrode conductive paste still maintains good coating performance at a high solid content, while enhancing the flexibility of the pole piece. The dispersed anti-cracking integrated auxiliary agent effectively disperses the positive electrode active material particles and prevents cracking through the action of its polar groups on the surface of the positive electrode active material, while maintaining the viscosity and solid content of the positive electrode conductive paste. The high solid content achieved by the synergistic work of the above three is conducive to significantly improving the process efficiency. The flexibility of the pole piece avoids the brittle fracture of the pole piece under high compaction density, and the optimization of the pole piece conductive network improves the conductivity and charge and discharge performance of the battery cell. The synergistic effect of all the above components improves the dispersion stability of the positive electrode conductive slurry, and solves the problems of easy cracking of the pole piece, poor brittleness of the rolled pole piece, easy breakage of the belt during rolling, cracking and light transmission of the R angle inside the hot-pressed battery cell, difficulty in cell wetting, and other manufacturing process windows and poor fast charging performance.

[0110] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode conductive slurry, comprising a solid and a solvent, characterized in that: In terms of solid mass percentage, the solid includes: 0.02% to 0.05% single-walled carbon nanotubes; 0.3% to 0.7% carbon black conductive agent; 0.1% to 0.5% softener; 0.1% to 0.5% of a dispersed anti-cracking integrated additive; 96% to 98% positive electrode active material; 1% to 2.25% binder.

2. The positive electrode conductive paste according to claim 1, characterized in that: The solid content of the positive electrode conductive slurry is 60% to 70%, and / or the viscosity of the positive electrode conductive slurry is 4000 to 30000 mPa.s, and the fineness of the positive electrode conductive slurry is less than 30 μm; and / or the solvent is N-methylpyrrolidone; and / or during the coating process of the positive electrode conductive slurry, when the positive electrode conductive slurry is coated at a coating rate of 20 m / min to 100 m / min, the obtained positive electrode sheet maintains an appearance without cracks.

3. The positive electrode conductive paste according to claim 1 or 2, characterized in that: The structural formula of the softener is: The main chain is selected from any one of the polyether linear segments of ethylene oxide, propylene oxide, and butylene oxide homopolymers or copolymers; R1 is selected from carboxyl, hydroxyl, and NH 4+ Any easily ionizable small molecule polar group; R2 is C1~C 100 Linear polyester segments or C1~C 100 linear polyether segment; preferably the molecular weight of the softener is 10000 to 500000.

4. The positive electrode conductive paste according to any one of claims 1 to 3, characterized in that: The dispersing and cracking prevention integrated auxiliary agent is a polyphosphate dispersant and / or a polysulfonate dispersant, and the structural formula of the polymerized monomer of the polyphosphate dispersant is: Among them, R 1 Any one selected from carboxyl, hydroxyl and hydrogen; R 2 C1~C 50 Linear polyolefin segments; R 3 Part of the benzene ring is irregularly substituted with C1~C 50 Linear polyether segments; Preferably, the molecular weight of the polyphosphate dispersant is 10,000 to 500,000.

5. The positive electrode conductive paste according to claim 1, characterized in that: The positive electrode active material is a lithium iron phosphate material containing a carbon coating layer.

6. The positive electrode conductive paste according to claim 1, characterized in that: The carbon black conductive agent is conductive carbon black and / or superconducting carbon black.

7. The positive electrode conductive paste according to claim 1, characterized in that: The binder is an adhesive obtained by copolymerization of polytetrafluoroethylene and hexafluoropropylene or a PVDF binder.

8. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material coating, wherein the positive electrode active material coating is obtained by coating a conductive slurry on the positive electrode current collector and then drying the conductive slurry, characterized in that: The conductive paste is the positive electrode conductive paste according to any one of claims 1 to 7.

9. The positive electrode sheet according to claim 8, characterized in that: The coating double-sided surface density of the positive electrode sheet is greater than 500g / m 2 , compaction density> 2.5g / cc, the positive electrode sheet after rolling, the peeling force after rolling is greater than 5N / m, the film resistance after rolling is less than 1mΩ, and the surface density is extended to 4-10g / m 2 The positive electrode sheet is manually folded and rolled at least 4 times without cracking and light transmission; the length extension rate of the positive electrode sheet in the running direction is 0.5% to 1.5%, and the width extension rate of the positive electrode sheet is 0.4 to 1.5 mm.

10. A lithium ion battery, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 8 or 9.

Citation Information

Cited By

  • Polyether modified phosphate dispersing agent and application thereof

    CN120149413A

  • Functional carbon nanotube conductive paste and preparation method thereof

    CN121097081A